Beliefs about poetry among 1st-year and final-year undergraduates in Early Childhood Teaching - Neira Piñeiro, María del Rosario; Martín-Macho Harrison, Ana (Didáctica. Lengua y Literatura, 2022)
In order to find out the beliefs that the students in the Degree in Early Childhood Education hold about poetry and its didactics, a qualitative-quantitative questionnaire was applied to 144 1st-year and 83 4th-year students from the universities of Oviedo and Castilla-La Mancha (Spain), on their conception of poetry, their beliefs about teaching it and their perception of their training. They all prioritize the emotional dimension of poetry and highlight the importance of a good oral transmission, but 1st-year students show prejudices regarding the difficulty of poetry, tend to instrumentalize poetic texts and do not know how to provide infant pupils with them. The 4th-year students are more aware of the aesthetic qualities of the poem and reveal some training in the didactics of poetry, although they claim to have an insufficient knowledge of works and text-selection criteria. It is concluded that the degree has both provided an acquaintance with the teaching of poetry and modified certain beliefs, although some training deficiencies and demands persist.
Keywords: Literary education; poetry; teacher training; early childhood education; beliefs